Clinical outcomes of quadrant root planing versus full-mouth root planing - P.-M. Jervøe-Storm (journal of clinical periodontology, 2006)
Objectives: To determine the clinical effects of full mouth compared with quadrant wise scaling and root planing. Method: Twenty patients with chronic periodontitis (X2 teeth per quadrant with probing pocket depths (PPD)X5mm and bleeding on probing (BOP) were randomized into a test group treated in two sessions with subgingival scaling and root planing within 24 h (full-mouth root planing (FMRP)) and a control group treated quadrant by quadrant in four sessions in intervals of 1 week (quadrant root planing (QRP)). PPD, relative attachment level (RAL) and BOP were recorded at baseline, 3 and 6 months. Results: Analysing first quadrant data, in moderately deep pockets (5mm4PPD o7 mm) there was no evidence for a difference (FMRP–QRP) between both groups for PPD reduction (mean: 0.128 mm; CI: [ 0.949, 0.693]; p50.747), RAL gain (mean: 0.118 mm; CI: [ 0.763, 1.000]; p50.781), and BOP reduction (mean: 20.1%; CI: [ 44.3, 4.2]; p50.099). Likewise, no significant differences between treatments were found for initially deep pockets (PPDX7 mm), neither for first quadrant nor for whole mouth data. Conclusion: The results of the present study demonstrated equally favourable clinical results following both treatment modalities.